Hybrid Materials: Electronic and Optical Excitations at the Pyridine/ZnO(101¯0) Hybrid Interface (Adv. Theory Simul. 2/2019). Issue 2 (4th February 2019) - Turkina, Olga; Nabok, Dmitrii; Gulans, Andris; Cocchi, Caterina; Draxl, Claudia
Abstract : Hybrid systems, combining inorganic and organic components, present an ex‐citing pathway towards tailoring materials with specific desired properties. By a first‐principles approach based on many‐body Green function techniques, in article number1800108, Olga Turkina, Claudia Draxl, and co‐workers explore the opto‐electronic spectra of pyridine/ZnO(1010). In this prototypical hybrid system, various kinds of novel exciton types are formed. The image shows the hole probability distribution of a hybrid charge‐transfer exciton.